Treatment of Non-small Cell Lung Cancer with EGFR-mutations - Kazue YONEDA; Naoko IMANISHI; Yoshinobu ICHIKI; Fumihiro TANAKA (Journal of UOEH, 2019)
Abstract: The discovery of activating mutations in the epidermal growth factor receptor (EGFR) gene and development of tyrosine kinase inhibitors (TKIs) of EGFR have achieved a paradigm shift in treatment strategy of non-small cell lung cancer (NSCLC). For advanced NSCLC harboring activating EGFR mutations, an EGFR-TKI is preferably prescribed as it provides a superior survival benefit over platinum-based chemotherapy. To further improve the therapeutic outcomes, more potent EGFR-TKIs through irreversible inhibition of tyrosine kinase have been developed. In a recent clinical trial, an irreversible EGFR-TKI (osimertinib) showed a superior survival benefit with lower toxicity profile. In addition, combination treatments such as an EGFR-TKI plus platinum-based chemotherapy may achieve a long-term survival. For earlier-stage resectable NSCLC with EGFR-mutations, several clinical trials to assess the efficacy of EGFR-TKIs in pre-operative induction setting and in postoperative adjuvant setting are now ongoing. Here we review and discuss the current status and future perspectives of treatment for EGFR-mutated NSCLC.